Cracks suppression strategies for CoCrNi medium entropy alloy fabricated by laser directed energy deposition. (February 2023) - Bi, Xiaolin; Li, Ruifeng; Li, Taotao; Zhang, Xiancheng; Cheng, Jiangbo; Tian, Yingtao
Graphical abstract: Highlights: Crack-free CoCrNi laser directed energy deposition additive parts successfully obtained at high heat input. High-angular grain boundary stress concentrations and excessive oxygen content in the additive parts were the main reasons for the crack formation. Three crack suppression strategies could be proposed from this study, namely, reducing the heat input, performing additive experiments under argon-filled environment, and decreasing the oxygen content of the powder. Abstract: Laser-directed energy deposition (l -DED) additive manufacturing of the CoCrNi medium entropy alloy is prone to cracking, especially with high laser heat input. Electron backscatter diffraction analysis showed crack formation and stress concentration at the high-angle grain boundaries. In addition, element content test results exhibited a higher oxygen content in the additive parts with high laser heat input. Electron probe X-ray microanalysis indicated that the oxygen was distributed uniformly in the additive parts. Corresponding molecular dynamics simulation results revealed that an increase in oxygen content led to a decrease in the tensile strength of the additive parts. Two methods of argon-filled environment l -DED experiments and low-oxygen CoCrNi feeding power (argon gas atomization) were used. Results showed that the number and size of cracks were significantly reduced in the additive parts obtained by a high heat input process when the l -DED was conducted in an argon-filled atmosphere and when powders with lower oxygen content were used. For the crack-free additive parts, the ultimate tensile strengths reached 625 MPa with high laser heat input. Three crack suppression strategies could be proposed from this study, namely, reducing the heat input, performing additive experiments under argon-filled environment, and decreasing the oxygen content of the powder.